+0

# Find the length of the shortest altitude of a triangle with side lengths 10,24,26

+5
37
1231
2
+1760

Find the length of the shortest altitude of a triangle with side lengths 10,24,26

Mellie  Nov 12, 2015

#1
+78577
+15

Look at the following pic, Mellie

Angle ABC can be found thusly :

sin CAB/ 26 = sin ABC / 24

And sin CAB = sin90 = 1

So

Sin ABC = 24/26

arcsin (24/26)  = ABC

And the altitude  AX drawn from A to to side BC will be one leg ot the right triangle AXB........so this altitude will be shorter than the altitude drawn from B  to side AC, since this altitude is the hypotenuse of triangle AXB. And AX will clearly be shorter than the remaining altitude drawn from C  to side AB.

And we can find AX thusly

AX / sinABC = AB / sin AXB

AX / sin[arcsin(24/26)]  = AB / sin AXB

But AXB = 90 so the sine of this angle  = 1   and   AB = 10.....so we have

AX = 10 * sin[arcsin(24/26)]  = 120/13 units  = about 9.23 units

And this is the shortest altitude

CPhill  Nov 13, 2015
Sort:

#1
+78577
+15

Look at the following pic, Mellie

Angle ABC can be found thusly :

sin CAB/ 26 = sin ABC / 24

And sin CAB = sin90 = 1

So

Sin ABC = 24/26

arcsin (24/26)  = ABC

And the altitude  AX drawn from A to to side BC will be one leg ot the right triangle AXB........so this altitude will be shorter than the altitude drawn from B  to side AC, since this altitude is the hypotenuse of triangle AXB. And AX will clearly be shorter than the remaining altitude drawn from C  to side AB.

And we can find AX thusly

AX / sinABC = AB / sin AXB

AX / sin[arcsin(24/26)]  = AB / sin AXB

But AXB = 90 so the sine of this angle  = 1   and   AB = 10.....so we have

AX = 10 * sin[arcsin(24/26)]  = 120/13 units  = about 9.23 units

And this is the shortest altitude

CPhill  Nov 13, 2015
#2
0

There is an easier way to solve the problem. You know that the triangle is a right triangle because it's sides are a Pythagorean triple. Saying this we can call the point perpendicular to B as X. Then we will call AX = y and CX = 26 - y. BX we will call a. Then using the Pythagorean Theorem y ^ 2 + x ^ 2 = 10^2, y^2 + x^2 = 100. Then we can make another equation using the other triangle. (26 - y)^2 + x ^ 2 = 24^2. This simplifies to x^2 + y^2 - 52y = -100. Plugging in information from the other equation 100 - 52y = -100. y = 50/13. Then plugging this in x = 120/13

Guest Jul 7, 2016

### 3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details